Using Artificial Intelligence to classify osteoarthritis in the knee joint: Review - Huthaifa A. Ahmed; Emad A. Mohammed (NTU Journal of Engineering and Technology)
Knee osteoarthritis (KOA) is a disorder that predominantly affects the cartilage in the human knee joint. In leg mobility, cartilage plays a vital function. In osteoarthritis The cartilage's top layer crumbles and impairs, causing excruciating agony. A patient with knee discomfort should see a doctor, who will assess the patient's clinical symptoms and recommend that the patient undergo radiographic imaging of the knee. In the therapy of osteoarthritis, clinical symptoms are quite important. Clinical symptoms and radiological criteria are used to do a proper examination of the disease. The breadth of the joint space, osteophytes, and sclerosis are all important radiographic criteria. Based on radiological data, the Kellgren-Lawrence (KL) scoring system is used to evaluate the severity of the condition. The KL system is the most widely used approach for grading Osteoarthritis (OA) in the knee joint into five separate classes, primarily to determine the severity of the illness. (Normal, Doubtful, Mild, Moderate, Severe).